The science inside the child : - Meadows, Sara (Routledge, 2016)
This engaging book presents some of the ways in which science can describe and explain how and why children develop in the way they do. It looks at children’s individual development within the development of our species, at genes, at the hormone systems that flood our bodies, at the neuroscience of children’s brains, and at patterns of behaviour. It looks, in other words, at the different influences on child development according to the scientific disciplines of evolutionary theory, genetics, epigenetics, endocrinology, neuroscience, epidemiology and psychology.